PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAAN KERJA KARYAWAN - Khairunnisa Dwi Permatasari; Suharini (Jurnal Riset Multidisiplin Edukasi, 2025)
PT XYZ as a forestry company lacks systematic documentation regarding employee job satisfaction levels, particularly related to the influence of leadership styles and work environment. This study aims to analyze the influence of leadership styles and work environment on employee job satisfaction at PT XYZ both partially and simultaneously. This study employed a quantitative approach with descriptive method involving 42 employees using saturated sampling technique. Data were collected through Likert scale questionnaires and analyzed using multiple linear regression. Work environment significantly influences job satisfaction (t count 4.280 > t table 2.023; sig. 0.001 < 0.05) with regression coefficient 0.480. Leadership style has positive but insignificant influence (t count 0.637 < t table 2.023; sig. 0.528 > 0.05) with coefficient 0.076. Simultaneously, both variables significantly influence (F count 19.249 > F table 3.23) with 47.1% contribution to job satisfaction.  Work environment has dominant influence on employee job satisfaction. Management is advised to prioritize work environment improvement and develop comprehensive leadership development programs.